The developing speciality coffee businesses of Bangkok, Thailand and Penang, Malaysia. A story of entrepreneurial passion and creativity? - Mark Azavedo; Art Gogatz (Journal of Entrepreneurship, Management and Innovation)
Purpose: This paper considers the recently emergent speciality coffee industry in Bangkok, Thailand and Penang, Malaysia. It addresses the research questions of what are the motivations and attitudes of small, entrepreneurial, speciality coffee business owners in both countries. Methodology: The study’s methodology was interview-based qualitative data gathering with no pre-determined hypotheses. Interviews were semi-structured. Questions considered motivations and attitudes variously but particular points of focus were passion and creativity. Analysis was through thematic content analysis. Findings: The main findings were that participants considered themselves to be passionate and creative, wanted to educate about coffee (the primary finding) and have no expectation and little hope of becoming wealthy through their coffee enterprises. Their focus was on other elements of happiness than money. It transpired that their passion was not an entrepreneurial passion, financially driven, but a passion for craft skills and production, and attendant lifestyles that were simply not concerned about income maximisation. Implications for theory and practice: It presents a potential view of entrepreneurship at major variance with the views of classical economics. Few entrepreneurs interviewed saw their businesses as having potential for wealth creation. Concerns to maximise income or profit were not prevalent. These were not the financially driven entrepreneurs of classical economics. Their focus was on their craft and its skills. All understanding of the mindset of the small speciality coffee business owners and creators is an insight of substantial practical importance, for instance, to those seeking to supply to them and perhaps other similar small businesses, or to advise them, including Government and Local Government advisory services. Originality and value: The question set for this study had never been asked before, so the study is unique within the industry. Its value lies in two areas, the practical real world of business, as mentioned, and for future researchers in entrepreneurship. With these small businesses built from lifestyle concepts rather than classical economic concepts, notably of income or profit maximisation and scale appropriate to those, strong doubt is thrown on the validity of those classical economic views. An important value in this study is precisely that it drilled down and struck a plethora of motivations and attitudes informally held by entrepreneurs, people of a type that do not usually inform studies of entrepreneurship but may inform future researchers, particularly when reviewing the growing body of small artisanal and craft businesses.